Pengaruh Penerapan Akuntansi Sektor Publik Dan Pengawasan Internal Terhadap Kinerja Instansi Pemerintah Daerah Dengan Good Governance Sebagai Variabel Intervening - Familia Irene, Bella; Iriyadi, Iriyadi; Hasibuan, David; Saurmauli Pangaribuan, Windawaty (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2024)
The aim of this research is to determine the mediating influence of good governance on the influence of the implementation of public sector accounting and internal supervision on the performance of local government agencies. The author conducted research at RSUD R. Syamsudin, S.H. Sukabumi City, which is located on Jalan Hospital No.1, Cikole, Kec. Cikole, Sukabumi City, West Java Province. The research results concluded that: (1) The application of public sector accounting has an effect on good governance; (2) Internal supervision influences good governance; (3) Good governance influences the performance of local government agencies; (4) The implementation of public sector accounting has a positive effect on the performance of local government agencies; (5) Internal supervision has a positive effect on the performance of local government agencies; (6) Good governance mediates the influence of the implementation of public sector accounting on the performance of local government agencies; and (7) Good governance mediates the influence of internal supervision on the performance of local government agencies.